Comparison of Finite Element and Finite Difference Methods for Two-dimensional Magnetotelluric Modelling - ถิ่นถาน ธนกฤษ; สาระคร วีระชัย (KKU Science Journal, 2017)
In this research, we compare the efficiency and accuracy of the finite difference and finite element methods for two-dimensional magnetotelluric modelling. The five-points finite difference method and finite element with triangular and quadrilateral meshes are derived and their computer codes are developed. To present the comparison of these methods, the half-space and COMMEMI2D-1model are used as the examples. The efficiency in term of CPU time and accuracy in term of numerical errors of three methods are presented and investigated. The obtained results indicate that the finite difference method takes the shortest CPU times to complete the task whereas the finite element method with quadrilateral mesh takes the longest CPU times. However, theapproximated solutions and their errorsobtaining by three methods are closed when the tested models are not too complicated.